Dampak Hilirisasi Terhadap Pendapatan Petani Kelapa Sawit di Nagari Talang Binjai Kecamatan Silaut Kabupaten Pesisir Selatan - Anggelin Rahmadani; Saputra, Megi; Firdaus, Nil; Pasrizal , Himyar; Elvina, Annisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the impact of downstreaming on the income of oil palm farmers in Nagari Talang Binjai, Silaut District, Pesisir Selatan Regency. The main problem in this research is the extent to which palm oil downstreaming helps increase the income of oil palm farmers in Nagari Talang Binjai, Silaut District, Pesisir Selatan Regency. This type of research is field research with a qualitative approach. The data analysis technique used is Miles and Huberman which includes reduction, presentation and drawing conclusions. The results of this research found that the downstreaming of palm oil stabilized the selling price of palm oil to farmers. Which can help stabilize the income of oil palm farmers in Nagari Talang Binjai, Silaut District, Pesisir Selatan Regency. Moreover, the European Union is boycotting palm oil commodities and their derivatives produced in Indonesia. After discussion, the Indonesian government must continue to carry out research regarding downstream palm oil and increase its costs. This is so that scientists can immediately produce one hundred percent vegetable energy, whether in the form of diesel or fuel, even in other forms of vegetable energy. After that, mass production of every vegetable energy product from palm oil will be carried out as soon as possible. Due to economic threats from abroad in the form of boycotts, reducing imports and planting oil palm, several countries have begun to implement them. By downstreaming palm oil, Indonesia will become a developed and strong country, and can bring prosperity to its people, especially oil palm farmers in Nagari Talang Binjai, Silaut District, Pesisir Selatan Regency.